Improved method of determination of economic efficiency of construction and operation of high speed mainline in Ukraine - Barash, YU. S.; Momot, A. V. (Science and Transport Progress, 2014)
Purpose. To develop an advanced methodology and formulate the measures concerning the definition of economic efficiency of high-speed movement organization taking into account the operating experience of rapid transportations in Ukraine, travel time, number of stops on the route, schedule and the demand for these transportations. Methodology. The economic feasibility for appropriateness of high-speed movement organization in Ukraine is an investment project, which involves step-by-step money investment to the construction. To solve such problems one uses net present value, which UZ or newly created companies can get during the project realization and after its completion. Findings. On the basis of obtained studies one can state that the methodology of complex determination of construction efficiency and high-speed passenger trains operation taking into account the cost of infrastructure, rolling stock, impact of environmental factors, etc. was developed in the article. Originality. We propose a scientific approach to determine the economic efficiency of the construction and high-speed main lines operation. This approach, unlike the existing one, includes the improved principles of determining the passenger traffic, the cost of high-speed mainline construction, the number of rolling stock; optimizes income and expenditure calculations in the context of competitive advantages and impact of the external factors on the company. For the first time it was taken into account the transit flow of passengers departing from CIS countries to the vacation in the Crimea, the Carpathians, Odessa and Lviv regions. The account of these factors increases the feasibility of administrative decisions concerning ensuring the efficiency of high-speed traffic functioning. Practical value. The proposed methodology and the research results allowed determining the construction reasonability of high-speed mainline for the passenger trains with a speed at least250 km/h inUkraine. This will allow the high-speed passenger traffic to occupy its niche in the transport market ofUkraine.